1987
DOI: 10.1017/s0950268800062075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time in lairage on caecal and carcass salmonella contamination of slaughter pigs

Abstract: A longitudinal study of the effect of time spent in lairage on salmonellas in the caecum and on the skin surface of 450 slaughter pigs from a single producer was conducted. Pigs were tested in 6 groups at 2 abattoirs, with one-third of a group being slaughtered after 18 h, one-third after 42 h and one-third after 66 h spent in lairage. The salmonella isolation rate from caeca and carcass surfaces increased significantly with increasing time spent in lairage. Salmonellas were isolated from the caeca of 18.5% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
47
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 4 publications
7
47
0
Order By: Relevance
“…Whenever pigs waited in lairage at the slaughterhouse, an increase in the contamination rate was shown by studies which compared slaughtering on the farm and at the slaughterhouse [15,16]. A study carried out in 1987 also showed that contamination increased with the time spent in lairage, but the times compared (18 h, 42 h and 66 h) are very different from current reality [22]. Three hours in lairage was the reference level considered in the present study.…”
Section: Discussionmentioning
confidence: 55%
“…Whenever pigs waited in lairage at the slaughterhouse, an increase in the contamination rate was shown by studies which compared slaughtering on the farm and at the slaughterhouse [15,16]. A study carried out in 1987 also showed that contamination increased with the time spent in lairage, but the times compared (18 h, 42 h and 66 h) are very different from current reality [22]. Three hours in lairage was the reference level considered in the present study.…”
Section: Discussionmentioning
confidence: 55%
“…Salmonella typhimurium is also a leading cause of foodborne illness in humans (Todd, 1989 ). The ability of infected swine to persist in a subclinical carrier state, yet shed large numbers of Salmonella during periods of stress (Hansen et al, 1964;Williams and Newell, 1970;Morgan et al, 1987) makes them an important reservoir of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Many Salmonella outbreaks are associated with meat and poultry (20), with contamination usually resulting from the carcass coming into contact with the feces of a Salmonella-infected animal during processing (22).…”
mentioning
confidence: 99%